Durability of reactive magnesia-activated slag-stabilized low plasticity clay subjected to drying–wetting cycle. Issue 2 (7th February 2016) - Du, Yan-Jun; Bo, Yu-Lin; Jin, Fei; Liu, Chen-Yang
Abstract : The strength characteristics and hydration products of reactive magnesia (MgO)-activated ground-granulated blast-furnace slag (GGBS) cement and concrete have been extensively investigated in previous studies. However, very limited study has comprehensively investigated the impacts of drying–wetting cycle on the engineering properties of GGBS–MgO-stabilised soils. This paper presents details of a study dealing with the influences of drying–wetting cycle on the dry density, pH, unconfined compressive strength ( q u ) and secant modulus ( E 50 ) of GGBS–MgO-stabilised kaolin clay. For the purpose of comparison, the conventional Portland cement (PC)-stabilised kaolin clay is selected as a control sample. Several series of and drying–wetting durability and unconfined compression tests were conducted for the stabilised soils. The variations in dry density, mass loss, pH, q u and E 50 with drying–wetting cycle are discussed. The results show that the GGBS–MgO-stabilised kaolin clay display higher dry density (~1–7%) and lower mass loss (~10–30%) than the PC-stabilised kaolin clay. The pH values and q u of the GGBS–MgO-and PC-stabilised kaolin clay decrease with the increase of drying–wetting cycle. When cured for 93–120 days under the controlled temperature of 20 °C and relative humidity of 95%, the GGBS–MgO-stabilised kaolin clay exhibits higher (~1.5 times) q u than the PC-stabilised kaolin clay. However, when the drying–wetting cycle exceeds forth, the GGBS–MgO-stabilised kaolin clay displays lower q u or E 50 than the PC-stabilised kaolin clay. The measured soil pH has a good linear relationship with q u of the soils that experienced drying–wetting durability tests. Finally, the mechanisms underneath the gradual loss of q u or E 50 with increasing drying–wetting cycle are discussed.